Constructing the female coffee farmer: Do corporate smart‐economic initiatives promote gender equity within agricultural value chains?. Issue 1 (22nd October 2018) - Lyon, Sarah; Mutersbaugh, Tad; Worthen, Holly
Abstract : The quest for gender economic equality is becoming a component of corporate and transnational institutional antipoverty initiatives in the Global South. Framed as "smart economics, " this approach explicitly ties women's empowerment to economic growth. On one hand, this framework employs a discursive construction that depicts women as attentive, family‐oriented entrepreneurs and caregivers who are more likely than their male counterparts to invest in their household and in their children's future; on the other hand, it involves a set of practices that register and reward women's participation. The smart‐economics movement operates on both public and private registers, ranging from women‐oriented government welfare programs to NGO‐managed microcredit schemes and, in this article, corporate actors and public–private partnerships engaged in agricultural value chains. Here we examine recent smart‐economic coffee industry initiatives, namely, a case study of microbatched "women's coffee" projects such as Allegro Coffee's Café La Dueña. We explore how coffee‐market value‐chain discourses and economic actions affect gendered ideologies and agricultural practices in coffee‐producing communities. We compare the impact on members of an Oaxacan (Mexican) fairtrade, organic producer organization that has implemented a women's microbatching coffee initiative relative to other organizations that have not adopted such programs. We find that although the program fails to demonstrate improvements in gender equity by reducing agricultural asset gaps or enhancing women's economic decision‐making power, landownership, or access to important agrotechnical services, it does lead to practical changes that are positively correlated with an increase in women's organizational participation, an openness of both women and men to gender‐equity programs and services, and women's increased access to land titles. Smart‐economic depictions of women as caring entrepreneurs also found a mixed reception in coffee communities: although women producers agreed with the notion that their coffee is superior, their risk aversion countered the entrepreneurial imaginary.